Clifford W. Beers - Hans Oh; Jordan DeVylder (Social Work and Society, 2013)
Clifford Beers considered the various methods of ending his life -each uniquely dreadful in its own way -and decided that falling from three stories high would be the least unpleasant. The anxiety and paranoia encroaching upon him became unbearable, and suicide seemed the only escape. And so he gripped the windowsill and dangled along the side of his family's home in New Haven, Connecticut, oblivious to the fact that he was destined to survive and become a great leader, which was made possible by a fortuitous patch of earth that broke his fall along with most of the bones in his feet.